Caracterización y microencapsulación de compuestos bioactivos del mortiño (vaccinium floribundum, kunth) - Guerra Vaca, Cristina Lucía (2017)
The investigation presented in this degree project was divided in two phases. The first phase had the purpose to characterize the bioactive compounds found in mortiño Vaccinium floribundum Kunth berries. Three samples from Quinticusig, Sigchos, Cotopaxi with different growing altitudes were studied to analyze the difference in the content of total polyphenols, flavonoids, anthocyanins and antioxidant capacity. The bioactive compounds were extracted using solutions methanol water formic acid and buffer solutions pH 1,0 potassium chloride 0,2Nand chlorhydric acid 0,2N and pH 4,5 sodium acetate 1M and chlorhydric acid1,0N. Both antioxidant capacity and concentration of bioactive compounds were determined by extracts and using spectrophotometry UV-VIS. A complete randomized block design with three repetitions and a mean separation test using Tukey 5 percent was made. Sample 1 with an altitude of 3020 masl presented the highest concentration of total polyphenols, the value was 66,83 mg gallic acid 100 g dried basis and an antioxidant capacity of 3670, 43 mg Trolox 100 g dried basis. Sample 3 found at 2850 masl followed with 55,22 mg GA 100 g DB and an antioxidant capacity of 3479,83 mg Trolox 100 g DB. Finally, sample 2 at an altitude of 2680 masl presented 45,83 mg GA 100 g DB and 3414,97 mg Trolox 100 g DB. A phenolic compound profile was performed using high performance liquid chromatography HPLC at two different wavelengths 280 and 330 nm, thirteen peaks were observed. Using standards, five peaks were correctly identified. They responded to caffeic acid, myricetin, p-hydroxybenzoic acid, catechin and vanillic acid. The tentative quantification assumed that vanillic acid and catechin were the phenolic compounds with higher concentration in the samples. The second phase of the investigation consisted on the microencapsulation of the mortiño freeze dried fruit in its totality by complex coacervation method. The microencapsulation pH was 4,5 and the concentration of the gelatin arabic gum solution was 3 percent. In a final instance, the microcapsules were evaluated qualitatively. These were round and didn’t present any openings or pores in their structure.